Acetylcholine Receptors : Revised Estimates of Extrajunctional Receptor Density in Denervated Rat Diaphragm - Fambrough, Douglas M. (The Rockefeller University Press, 1974)
The number of extrajunctional acetylcholine receptors ((125)I-labeled α-bungarotoxin binding sites) per unit length of muscle fiber and the average fiber circumference were determined for rat diaphragm muscle fibers denervated 0, 2, 4, 7, 10, and 14 days. From these data receptor densities (sites per square micrometer of surface) were calculated. Values thus obtained were considerably lower than those estimated previously by autoradiography. Receptor density increased from < 6 sites/µm(2) in innervated muscle to 635 ± 29 sites/µm(2) 14 days after denervation. The form of the relationship between receptor density and acetylcholine sensitivity and the time-course of change in receptor density after denervation are as previously reported.